Building Secure and Ethical AI Systems: A Comprehensive Guide - Rajkumar Sukumar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the fundamental aspects of building secure and ethical AI systems in today's rapidly evolving technological landscape. The article examines critical components including data security, privacy preservation, integrity verification, and ethical governance frameworks. It delves into advanced encryption protocols, access control mechanisms, privacy-preserving techniques, blockchain integration, and authentication systems while highlighting the importance of security-aware development lifecycles. The article synthesizes current research and industry best practices to provide organizations with actionable insights for implementing robust security measures and ethical considerations throughout the AI development process. Special attention is given to emerging technologies and methodologies that enable organizations to protect their AI infrastructure while ensuring regulatory compliance and maintaining stakeholder trust.
Keywords: Artificial Intelligence Security; Blockchain Integration; Data Privacy Protection; Ethical AI Governance; Secure Development Lifecycle